PENGARUH JIWA KEWIRAUSAHAAN, NILAI KEWIRAUSAHAAN TERHADAP PERILAKU KEWIRAUSAHAAN DAN KEBERLANGSUNGAN USAHA PADA SEKTOR UMKM - Oktafalia Marisa M (STIE Wiyatamandala, 2019)
Role of UMKN in National Economic was very important. About 99.9% of National Economic contributed by UMKM sector and it also contributed to create employement. UMKM also contributed 60.34% of GDP. And there is also potency to keep increasing as long as the number of entrepreneurship still growing. Government also takes it seriously to develop national entrepreneurship and boast up the potency of UMKM in Indonesia through BEKRAF. The problem is the internal aspect of the entrepreneur still lack of competency (entrepreneurship competency and social competency). Entrepreneurship competencies consist of some components which root deep inside the entrepreneur background such as the traits, characters, attitude, social role and self-image. Some external factors also contribute to developing entrepreneuship skill such as training, education and working experience. Entrepreneurship spirit was the soul of the entrepreneurship itself. And the entrepreneurship value was the prerequisite factors that develop the entrepreneuship behavior. This research takes 67 samples from UMKM young entrepreneur in West Jakarta. Result of this research concluded there is influence of Entrepreneurship Soul and Entrepreneurship Value to Entrepreneurship Behavior. And furthermore Entrepreneurship Behavior also has its influence to business sustainability of UMKM in West Jakarta.